ASEAN and the Challenge of Closer Economic Integration - Ponciano Jr. S. Intal (Philippine Institute for Development Studies (PIDS), 1997)
From a preferential tariff rate, ASEAN has decided to move to a free trade area by the first decade of the 21st century and the creation of an ASEAN economic region by the year 2020. Towards this end, member countries are expected to jointly address various trade concerns. Through unity and cooperation, ASEAN is hoped to become an even more important voice in the international arena.
Keywords: 330; tariff; economic openness; economic integration; free trade